BRIEF NOTES ON EDUCATION IN ALTANEIRA-CE: ADVANCES, CHALLENGES, AND PERSPECTIVES (REMUNOM, 2025)
This article presents a critical and in-depth analysis of basic education in the municipality of Altaneira, located in the hinterland of Ceará, Brazil. It aims to highlight the achievements, persistent challenges, and prospects for a quality, equitable, and inclusive public education system. The investigation is grounded in classical and contemporary education theorists such as Paulo Freire, Dermeval Saviani, Gaudêncio Frigotto, and José Carlos Libâneo, and is supported by data from official sources including INEP, Todos Pela Educação, SEDUC-CE, and UNESCO. The adopted methodology is analytical bibliographic research based on specialized literature, institutional documents, and up-to-date educational reports. The study reveals that, although Altaneira has made progress in literacy indicators, teacher training, and inclusive pedagogical practices, its public school network still faces obstacles such as limited financial and pedagogical resources, lack of qualified support professionals, transportation difficulties for rural students, and weak family engagement. In light of this scenario, the article offers recommendations for strengthening democratic management, increasing investments, ensuring continuous professional development, and promoting intersectoral collaboration. It concludes that overcoming educational inequalities in Altaneira requires territorialized public policies, strong social pacts, and an ethical commitment to education as a public good and a tool for social transformation.